2018
DOI: 10.32532/jori.v8i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Sarkoma Ewing

Abstract: Sarkoma Ewing/ Ewing Sarcoma (ES) merupakan keganasan tulang tersering nomor dua pada anak setelah osteosarkoma. Sebagai tumor dengan derajat keganasan tinggi, seringkali ES terdiagnosis dengan kondisi lesi yang ekstensif serta tidak jarang sudah mengalami metastasis sehingga prognosis pasien menjadi buruk. Tata laksana yang tepat untuk ES menjadi tantangan bagi klinisi dalam menangani pasien. Terapi multimodalitas berupa kombinasi antara kemoterapi, pembedahan dan radioterapi menjadi pilihan terbaik dalam tat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been found that treating some types of cancer with chemotherapy or radiation when combined with heat therapy is much more effective than by conventional cancer therapies alone [17][18][19][20]. The research conducted by Gozal and Djakaria [21] has shown promising results in the treatment of Ewing Sarcoma which is the second most common bone tumor, predominantly affecting individuals in the age range of 10 to 30 years. Through a combination of chemotherapy and thermotherapy, they increased the 5-year survival rate for patients from less than 10% to more than 60%.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that treating some types of cancer with chemotherapy or radiation when combined with heat therapy is much more effective than by conventional cancer therapies alone [17][18][19][20]. The research conducted by Gozal and Djakaria [21] has shown promising results in the treatment of Ewing Sarcoma which is the second most common bone tumor, predominantly affecting individuals in the age range of 10 to 30 years. Through a combination of chemotherapy and thermotherapy, they increased the 5-year survival rate for patients from less than 10% to more than 60%.…”
Section: Introductionmentioning
confidence: 99%
“…One of the locations of the ewing sarcoma tumor is in the bone in the lower arm (forearm). According to Gozal and Djakaria [10], using a combination of chemotherapy treatments, surgery, and treatment using radiotherapy or increased temperature in tumors, it can reduce the 5-year survival rate from <10% to >60% in patients with Ewing Sarkoma Tumor.…”
Section: Introductionmentioning
confidence: 99%